A Case Report of Facial Nerve Palsy in Kawasaki Disease - Shahrokh Rajaei; Hashem Lashgari Kalat; Niloofar Choobin; Masoud Kargar (Journal of Cardio-Thoracic Medicine)
Introduction: One of the most prevalent childhood vasculitis is kawasaki disease (KD), which mainly affects medium-sized arteries throughout the body. This disease usually does not cause many neurological symptoms and only rarely results in facial nerve palsy (FNP).Case presentation: A 4.6-month-old iranian girl presented due to a prolonged fever. Lab tests showed increased CRP, ESR, ferritin, WBC, and platelet counts, and echocardiography revealed dilated right and left main coronary arteries, without any vegetations, pericardial effusion, and atrioventricular valve regurgitation. The patient was diagnosed with incomplete KD. At the same time, she developed left-sided peripheral FNP. Patient treated with intravenous immunoglobulin and aspirin. The fever resolved after about 36 hours, and the patient was discharged on the 16th day of hospital admission. Follow-up echocardiography demonstrated gradually resolution of her coronary arteries dilation. FNP was recovered completely after about 2 months.Conclusion: FNP is an uncommon neurological symptom of KD. However, it typically resolves on its own and without any lasting effects in those who survive the illness. Nevertheless, it may indicate a higher likelihood of coronary artery involvement, and as a result, additional anti-inflammatory treatments and more closely monitored echocardiography may be necessary.